2013
DOI: 10.1002/jcp.24339
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic cooperation between PI3K/Akt signaling and transcription factor Runx2 promotes the invasive properties of metastatic breast cancer cells

Abstract: The serine/threonine kinase Akt/PKB promotes cancer cell growth and invasion through several downstream targets. Identification of novel substrates may provide new avenues for therapeutic intervention. Our study shows that Akt phosphorylates the cancer related transcription factor Runx2 resulting in stimulated DNA binding of the purified recombinant protein in vitro. Pharmacological inhibition of the PI3K/Akt pathway in breast cancer cells reduces DNA binding activity of Runx2 with concomitant reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…Zhang et al (13) previously reported that Mfn2 mediates the proliferation of pulmonary artery smooth muscle cells via the PI3K/Akt signaling pathway. Although there have been a number of studies on the PI3K/Akt pathway and breast cancer in recent years (21)(22)(23), none of these studies have demonstrated that the PI3K/Akt signaling pathway is downstream of Mfn2. Our data suggests that Mfn2 decreased Akt activity in the presence of E2, and that Akt is downstream of Mfn2.…”
Section: Mfn2 Suppresses Cell Cycle Progression Via the Pi3k/akt Signmentioning
confidence: 99%
“…Zhang et al (13) previously reported that Mfn2 mediates the proliferation of pulmonary artery smooth muscle cells via the PI3K/Akt signaling pathway. Although there have been a number of studies on the PI3K/Akt pathway and breast cancer in recent years (21)(22)(23), none of these studies have demonstrated that the PI3K/Akt signaling pathway is downstream of Mfn2. Our data suggests that Mfn2 decreased Akt activity in the presence of E2, and that Akt is downstream of Mfn2.…”
Section: Mfn2 Suppresses Cell Cycle Progression Via the Pi3k/akt Signmentioning
confidence: 99%
“…The peptide, residues 26 -38 phosphorylated at Ser28, was also observed without O-GlcNAc modification. Ser28 is phosphorylated downstream of ERK/MAPK, PI3K/Akt, and PTH/PKA pathways (17,21,58,59), and phosphorylation at this site has been implicated in PTH-induced expression of MMP13 (21) as well as invasive properties of metastatic breast cancer cells (58).…”
Section: Pharmacological Inhibition Of Oga Enhances Runx2 Activity Inmentioning
confidence: 99%
“…Such a phenotype has been suggested for breast cancer cells. 54 Indeed, RNASeq analyses of Runx2 k/in or Runx2 k/d cells revealed that multiple osteogenic genes were significantly increased in Runx2 k/in and decreased in Runx2 k/d MM cells. The osteogenic genes regulated included osteocalcin, OPN, DMP1, as well as osteoclast markers RANK, MMP-9, and CtsK.…”
mentioning
confidence: 99%